Recurring large deletion in DRC1 (CCDC164) identified as causing primary ciliary dyskinesia in two Asian patients. Issue 8 (4th July 2019) - Morimoto, Kozo; Hijikata, Minako; Zariwala, Maimoona A.; Nykamp, Keith; Inaba, Atsushi; Guo, Tz‐Chun; Yamada, Hiroyuki; Truty, Rebecca; Sasaki, Yuka; Ohta, Ken; Kudoh, Shoji; Leigh, Margaret W.; et al.
Abstract: Background: Primary ciliary dyskinesia (PCD) is a relatively rare autosomal recessive or X‐linked disorder affecting ciliary function. In the set of causative genes, however, predominant pathogenic variants remain unknown in Asia. Method: A diagnosis of PCD was made following a modern comprehensive testing including genetic analysis; targeted resequencing for screening variants, and Sanger sequencing for determination of the breakpoints, with an additional review of databases to calculate the deletion frequency. A multiplexed PCR‐based detection method has also been developed. Results: We ascertained a 50‐year‐old Japanese male who had been diagnosed with diffuse panbronchiolitis (DPB), but refractory to macrolide therapy. We reevaluated the case and identified a large homozygous deletion spanning exons 1 to 4 of the DRC1 and determined the breakpoints (NM_145038.4: c.1‐3952_540 + 1331del27748‐bp). In the PCD cohort at the University of North Carolina, we found a female PCD patient of Korean descent harboring the same homozygous deletion. From the Invitae testing cohort, we extracted four carriers of the same deletion among 965 Asian individuals, whereas no deletion was found in the 23, 951 non‐Asians. Conclusion: We speculate that the DRC1 deletion is a recurrent or perhaps founder mutation in Asians. The simple PCR method could be a useful screening tool. Abstract : Primary ciliary dyskinesia is a relatively rare autosomal recessive or X‐linked disorder affecting ciliary function, but predominant pathogenic variants remain unknown in Asia. We identified a large homozygous deletion spanning exons 1 to 4 of the DRC1 and determined the breakpoints in a Japanese male who had been diagnosed with refractory diffuse panbronchiolitis, and in another Korean patient. From the Invitae testing cohort, we extracted four carriers of the same deletion among 965 Asian individuals, whereas no deletion was found in the 23, 951 non‐Asians, indicating that the DRC1 deletion is a recurrent or perhaps founder mutation in Asians.